A Six-Channel Automated Platelet Aggregometer - Adams, J; Heptinstall, S; Mitchell, J. R. A (Thrombosis and Haemostasis, 1975)
A simple automated platelet aggregometer is described which allows six plasma samples to be handled concurrently.